Sistem Pendukung Keputusan untuk Menentukan Praja Terbaik Menggunakan Metode Simple Additive Weighting - Yogi K. Nurdin; Sarjon Defit (Jurnal Sistim Informasi dan Teknologi, 2020)
The Institute of Domestic Administration (IPDN) of the West Sumatra Campus is a tertiary institution attended by students from all over Indonesia. This activity is a mandatory activity for all cadets and must be followed every semester. Values ​​determine the graduation of a cadet in his education. For this reason, a good system is needed in determining the value. This study aims to find effective and appropriate values ​​in each service. The method used is Simple Additive Weighting for data that determine ranking. The results of this study have an accuracy of 85% of the ranking data manually to the test data. Thus, this system is more effective in the search process and ranking accuracy. Then this research is a system that can be used as a reference in ranking the best value of welfare.